Existential content of archetypes embodied in works of Bohdan-Ihor Antonych (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The system methods of artistic thinking of the poet is being monitored in the article, disclosed the identity of the poetic world and poetry codes. Lyrics gives a broad space for the analysis of archetypes within the framework subjective experience. It was illustrated that artistic and philosophical conception of the artist claims the unity of the world, the cosmos, including the man in the circle of life as an organic particle nature.It was proved that intimate, private, emphatically self-centered thematic-ideological core of Bohdan-Ihor Antonych heritage intertwines very closely with massive structures and archetypal images that are inherent in the deep layers of national consciousness. Creator raises the issue of subtle nuances of seeing the world, shifts in the consciousness of author’s “I”, which are realized in individual metaphors, built on rethinking archetypal images. Mythopoetic aspect of the analysis enabled the demonstration of flexibility and relevance of artist’s literary archetypes.Under the influence of historical and social changes any archetype fixed in literary works, reveals a fresh, timeless content “built in” author's intention and implemented in the poetry pieces. Archetype images are deeply rooted into personal consciousness of a lyric character and serve as a starting point for collecting associations, mythologem codes in different levels, ethnic, national and cultural reminiscence. Enormous semantic content richness, complex symbolic and figurative structure, exquisite metaphors, demanding time and space chimeras give a special sort of aesthetic pleasure while reading the works by B.-I. Antonych.
Keywords: archetypal structure; poetry conception of the world; poetics